Inflammatory CD11b+ Macrophages Produce BAFF in Spleen of Mice Infected with Leishmania donovani - Kazuki Nagai; Wataru Fujii; Junya Yamagishi; Chizu Sanjoba; Yasuyuki Goto (Pathogens, 2024)
Visceral leishmaniasis (VL) is an infectious disease caused by parasitic protozoa of the genus Leishmania and manifests clinical symptoms such as splenomegaly, hepatomegaly, anemia, and fever. It has previously been shown that B-cell-activating factor (BAFF) is involved in splenomegaly during VL. Although BAFF is known to be expressed by a variety of cells, the mechanism of elevated BAFF expression in VL is not clear. In this study, we aimed to identify BAFF-producing cells in the spleens of mice infected with Leishmania donovani. Splenocytes of L. donovani-infected mice showed elevated BAFF expression compared to that of naive mice. In the infected spleen, the number of both CD11b+ and F4/80+ cells increased, and the major BAFF-producing cells were CD11b+ cells, which did not serve as host cells of Leishmania. Immunohistochemical/immunofluorescent staining of spleens of infected mice revealed that the increased CD11b+ cells were primarily MRP14+ mononuclear cells. Together, these results suggest the increased BAFF expression in the spleen of L. donovani-infected mice involves a recruitment of inflammatory macrophages distinct from host macrophages for the parasites.